Enabling food system innovation: Accelerators for change - Thornton, Philip K.; Mason D'Croz, Daniel; Kugler, Cody; Remans, Roseline; Zornetzer, Heather; Herrero, Mario (Elsevier, 2024)
It is widely accepted that current food systems are not on a trajectory for achieving the Sustainable Development Goals by the end of the decade. Technological innovation will have a considerable role to play in different parts of the food system; many promising options exist or are in the pipeline, some of which may be highly disruptive to existing value chains. Scaling up the innovations required, at the same time as protecting those who may lose out in the short term, will require a strong enabling environment. Here we apply an existing framework of eight change accelerators to six case studies of historical agricultural innovation. We estimated the degree to which each accelerator had been addressed at some stage in the innovation process, as a measure of the gap between what was needed and what was achieved. For the innovations that are being taken to scale and widely utilized, these accelerator gaps are small. Uptake of other innovations is stalled, and for these we found large gaps for one or more of the eight accelerators. Impactful innovation processes address all eight change accelerators at some point, with different phasing of the accelerators depending on the nature of the technology and on the impact pathway being pursued. This simple framework, when used in combination with narratives of uptake based on theories of change and impact pathways, may provide an effective means of screening future innovation processes to help prioritize and guide investment that can lead to more resilient, sustainable and equitable food systems.